Analisis Motivasi Tenaga Kerja Indonesia (TKI) Melakukan Migrasi ke Kuala Lumpur (Studi Kasus di KBRI Kuala Lumpur) - Raden Biroum Bernardianto; Anggy Ria Sandita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to describe and analyze the motivation of Indonesian Workers (TKI) to migrate to Kuala Lumpur. The type of research used is qualitative research. Determination of informants at the initial stage of the researcher using accidental sampling techniques. Accidental sampling is a technique for determining samples based on coincidence, that is, anyone who accidentally meets with a researcher can be used as a sample is viewed by the person who happened to be found to be suitable as a data source. In this study, researchers conducted interviews with 39 informants. Data collection techniques are documentation, observation, and interviews. The results showed that the motivation of Indonesian Workers (TKI) to go to Kuala Lumpur was not only related to socio-economic motives such as low income levels of Indonesian migrant workers, length of employment in migrant workers, the age of migrant workers, the number of family dependents, status marriage, gender, ease of finding work, having a husband / family in Kuala Lumpur, adequate transportation, cheap education costs in Kuala Lumpur. Also related to the role of the Indonesian Embassy in Kuala Lumpur in handling troubled migrant workers.